Modern trends in evidence scholarship: is all rosy in the garden? - Jackson, John (Quinnipiac University School of Law, 2003)
This article reviews the state of evidence scholarship in the early 21st century and argues that it has been enriched by drawing upon a range of different disciplines including social psychology,cognitive science, forensic psychology, mathematics, linguistics and economics. It argues for the relevance of sociological, historical and comparative approaches as a useful corrective aganst the dominant optimism of the rationalist tradition of evidence scholarship.